Healthcare Providers’ Knowledge, Attitude, and Perspective regarding Diabetes Self-Management during Ramadan Fasting: A Cross-Sectional Study - Sh Sugiharto; Wiwiek Natalya; Bambang Widjanarko Otok (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Evidence shows that most general practitioners have low knowledge related to diabetes self-management during Ramadan fasting. However, studies on healthcare providers’ competencies related to diabetes self-management during Ramadan fasting are still rare.Purpose: This study aimed to investigate healthcare providers’ knowledge, attitude, and perspective concerning diabetes self-management during Ramadan fasting.Methods: The study applied a cross-sectional design and was conducted in forty-one (41) community health centers in Pekalongan, Central Java, Indonesia. The study participants were medical doctors, nurses, nutritionists, pharmacists, and public health officers. The total sampling technique was used. There were 205 healthcare providers who met the inclusion criteria. Their knowledge, attitude, and perspective were assessed using a questionnaire developed by Zainudin and Hussain. The Wilcoxon test was used to analyze the data. Results: The healthcare providers’ knowledge of Ramadan fasting was very low (36.79±26.11). More than half of the respondents (53.17%) advised diabetic patients to manage diabetes in general, although specific counseling for diabetic patients related to fasting in Ramadan month was not provided (55.12%). The perspective of Ramadan fasting among healthcare providers was moderate (62.68%±30.40). The results also showed that general and safe practice knowledge significantly affected the healthcare providers’ perspective toward Ramadan fasting (Z=-12.49, p=0.000), (Z=-12.02, p=0.000), respectively. Conclusion: Healthcare providers’ knowledge and attitude concerning diabetes self-management during Ramadan fasting were low. Accordingly, this affected their perspective. It is strongly recommended that a formal Ramadan fasting management training program should be given regularly to provide appropriate consultations and services.